Ultramicro-sized sputtered iridium oxide electrodes in buffered saline: Behavior, stability, and the effect of the perimeter to area ratio on their electrochemical properties. (10th August 2022) - Ghazavi, Atefeh; Cogan, Stuart F.
Highlights: 2 × 50 μm 2 sputtered iridium oxide (SIROF) ultramicro-sized (UM-sized) electrodes in ferrocene in acetonitrile at 5, 50, and 500 mV/s sweep rates form a sigmoidal-shape cyclic voltammogram indicating hemispherical diffusion of ferrocene. 4 × 50 μm 2 SIROF UM-sized electrodes in PBS have a longer transition time compared to micro-sized electrodes indicating more availability of counterions to UM-sized electrodes. SIROF UM-sized electrodes in PBS have a higher charge injection capacity (CIC), lower maximum driving voltage per unit current density, and lower specific AC impedance compared to micro-sized electrodes. Higher perimeter to area ratio (P/A) SIROF electrodes have lower maximum driving voltage per unit current density during pulsing and lower specific AC impedance. SIROF UM-sized electrodes can present long-term electrochemical stability over 10 9 current pulses. Abstract: Hemispherical transport of electroactive species to ultramicroelectrodes (UME) as opposed to linear transport to regular electrodes, makes them an attractive candidate for a variety of different applications such as sensors and neural electrodes. In this paper, ultramicro-sized (UM-sized) sputtered iridium oxide film (SIROF) electrodes' cyclic voltammogram in a buffer electrolyte with ionic counterions (phosphate-buffered saline (PBS)) is compared to their cyclic voltammogram in electrolytes with neutral electroactive species (ferrocene in acetonitrile), as they correspond to the use of UMEs as neural electrodes and sensors, respectively. To assess the behavior of SIROF UM-sized electrodes in PBS, their transition time, charge injection capacity (CIC), and specific impedance (voltage per unit current density) is compared to the corresponding quantities in microelectrodes. Moreover, the effect of the perimeter to area ratio (P/A) on the specific impedance and CIC of the UM-sized electrodes is evaluated to provide design guidance for their use as neural electrodes. The stability of SIROF UM-sized coating is assessed by subjecting the electrode to long-term continuous current pulsing and potential cycling. While cyclic voltammograms of SIROF UM-sized electrodes in ferrocene presented a steady-state current at slow sweep rates (< 500 mV/s), such behavior was not observed in PBS. However, the inflection points in the chronopotentiometric curve representing transition time were shorter for micro-sized SIROF electrodes compared to UM-sized electrodes once they were subjected to similar current densities. Also, SIROF UM-sized electrodes presented higher CIC and lower specific impedance compared to microelectrodes. SIROF UM-sized electrodes with larger P/A had lower specific impedance and higher CIC and their electrochemical properties could remain stable under long-term continuous pulsing and cycling.